Successful combined endoscopic treatment (photodynamic therapy+electrocautery) of patient with early cancer of lower third esophagus (14 year follow up) - V. V. Sokolov; Е. S. Karpova; Е. V. Filonenko; T. A. Belous; G. A. Frank (Biomedical Photonics)
The case of successful use of photodynamic therapy (PDT) combined with electrocautery for treatment of patients with cancer or lower third esophagous is reported. The patient had well-differentiated adenocarcinoma with underlying intestinal metaplasia and I– III displasya. The organ-preserving endoscopic treatment was performed: PDT with phogem (2 courses) combined with electrocautery of tumor (3 sessions). Photogem was administered i.v. in dose 3.0 mg/kg 48 h prior to each session of irradiation (635 nm, light dose 150 J/cm2). Three months after treatment additional PDT in described regimen was performed for residual tumor. The followup accounted for 14 years, the complete regression of esophageal tumor with good functional result without scar deformation and stenosis was observed.